Courage as Identity Work: Accounts of Workplace Courage - Koerner, Melissa M. (Academy of Management Journal, 2014)
This study focuses on the intersection of identity dynamics and workplace courage. I examine accounts of courage submitted by business professionals and articulate the identity processes underlying the accounts. The narratives illustrate four storylines that reflect four distinct forms of courage and one storyline that reflects a lack of courage. In the accounts, identity tensions precipitate courageous acts, and courage-based identity work is used to reconcile the tensions. The findings suggest that in accounts of workplace courage, courageous behavior is viewed as an important form of identity work that helps individuals to minimize incongruities between their self- and social identities.